Piezotronic Transistor Based on Topological Insulators - Lijie Li (ACS Nano, 2017)
Topological insulators are remarkable envisioned materials, with a potentially wide range of applications spanning from highly precise magnetic sensors to quantum computers. In this work, a novel transistor device based on the topological insulator structure has been postulated and subsequently analysed using the density function theory. It is found that the switching ratio can reach as high as 10^10, the highest reported so far.